Statistical analysis of corn consumption for improved mycotoxin exposure estimates for the population of Veracruz City, Mexico. Issue 5 (4th May 2017) - Wall-Martínez, H. A.; Ramírez-Martínez, A.; Wesolek, N.; Brabet, C.; Rodríguez-Jimenes, G. C.; García-Alvarado, M. A.; Salgado-Cervantes, M. A.; Robles-Olvera, V. J.; Roudot, A. C.
ABSTRACT: Corn consumption was evaluated in the population of Veracruz City, Mexico, through two different dietary intake questionnaires. The selection of 300 sampling locations was completely random. The population was segregated into gender and age categories. A daily consumption questionnaire was used to determine the consumption of corn tortillas and a frequency questionnaire to determine the consumption of other corn products. A book of photographs was used to adjust criteria on the size of the portions of corn products and a probability distribution was built of the weight and content of corn for tortillas . Probability density functions (PDFs) were used to describe the consumption of each corn product. Men and those between 14 and 65 years old have the highest consumption of tortillas. Tortillas, antojitos, tacos and chilaquiles are the products that provide the largest amount of corn to the Veracruz people's diet. Even though these products are nixtamalisated, there is evidence that after a thermo-alkaline process some contaminants such as mycotoxins (like aflatoxin, which is a mutagenic, teratogenic and carcinogenic toxin) could be present in high concentrations. These results highlight the need to characterise the consumption of one of the main foods included in dietary staple in Mexico as a first step for a probabilistic risk assessment.